2019
DOI: 10.1111/nyas.14109
|View full text |Cite
|
Sign up to set email alerts
|

Exploring associations between water, sanitation, and anemia through 47 nationally representative demographic and health surveys

Abstract: Globally, no countries are on track to achieve the adopted global nutrition targets set for anemia in 2025. Given the linkages between water, sanitation, and hygiene (WASH) and nutrition, this secondary data analysis explores potential associations with anemia. Forty‐seven demographic and health surveys were used to explore the association between unimproved water and sanitation and anemia in women and children with adjusted odds ratios (ORs) calculated by country and cumulatively. In over 60% of countries, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 41 publications
(47 reference statements)
8
34
1
5
Order By: Relevance
“…The 3 countries they selected were India, Burundi, and Senegal, where they adjusted for age, sex, residence, education, wealth, iron supplementation, and deworming. In alignment with our findings, they found all 3 countries showed an association between unimproved and shared sanitation facilities and higher odds of anemia, although 1 of the associations was nonsignificant ( 31 ). Additionally, they also found a mix of associations between water source and anemia ( 31 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The 3 countries they selected were India, Burundi, and Senegal, where they adjusted for age, sex, residence, education, wealth, iron supplementation, and deworming. In alignment with our findings, they found all 3 countries showed an association between unimproved and shared sanitation facilities and higher odds of anemia, although 1 of the associations was nonsignificant ( 31 ). Additionally, they also found a mix of associations between water source and anemia ( 31 ).…”
Section: Discussionsupporting
confidence: 91%
“…The authors found PSC exposed to unimproved sanitation facilities had higher odds of anemia compared to those who had improved sanitation facilities in 18 of 45 countries, adjusting for sex and age ( 31 ). Notably, the authors only conducted multivariable logistic regressions in 3 countries that showed strong unadjusted ORs and represented different parts of the world ( 31 ). The 3 countries they selected were India, Burundi, and Senegal, where they adjusted for age, sex, residence, education, wealth, iron supplementation, and deworming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding house and environmental factors, the current study reported that children living in mud house and open sewerage system areas are likely to be anemic. These results are supported by studies [32][33] that household type and living environment are the major contributing factors of anemia. Considering the association of the maternal knowledge of balanced diet, anemia causes and preventive measures, prevalence of anemia was found to be high among children, whose mothers had poor knowledge about these parameters.…”
Section: Regardingsupporting
confidence: 62%
“…Anemia is a leading cause of hospital admission, reduced cognitive development, growth, and poor immune function in children 7 , since the etiology and pathogenesis of anemia are complex 14 , caused by a multifactorial of factors. such as cancer; micronutrient de ciencies; infections, such as malaria and tuberculosis(TB) 15 . In HIV-infected children, the virus can infect parts of the bone marrow responsible for manufacturing red blood cells and erythropoietin, which is required to stimulate red blood cell production 16 .…”
Section: Introductionmentioning
confidence: 99%